PERAN GURU DALAM MENGATASI PERMASALAHAN MEMBACA PERMULAAN SISWA KELAS II SD NEGERI 12 BEMBAN PANGERSIT - Susilawati, Nini; Ason, Ason; Peterianus, Septian (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: The purpose of this research is to describe the teacher's role in overcoming students' early reading problems. The research subjects were class II teachers at SD Negeri Bemban Pengersit and the object of the study was beginner reading skills. This study uses a descriptive method with a qualitative approach. The data collection tools used were interview guides, observations and documentation. The results of the study show that in overcoming the problems of beginning reading, the teacher acts as a guide, coach, and companion for student learning activities. In its role as a mentor, the teacher tries to guide students so that they can discover their various potentials, especially the potential in beginning reading. As a teacher trainer trains students in the formation of basic competencies, according to their respective potentials. As a companion, the teacher accompanies and controls students in the class so that what is conveyed in the process of teaching and learning activities can be carried out properly. In the process of learning to read, the initial stage is the introduction of letters, then combining vowels and consonants into words and words and combining words into simple sentences. In addition, the teacher gives examples of pronunciation reading syllables, words, and simple sentences that are imitated and memorized by students. In order for students to be more helpful and facilitate students' reading pronunciation, the teacher gives assignments to students so they can study with their parents at home.Keywords: Teacher's Role, Beginning Reading Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan peran guru dalam mengatasi permasalah membaca permulaan siswa. Subjek penelitian adalah guru kelas II SD Negeri Bemban Pengersit dan objek penelitian adalah kemampuan membaca permulaan. Penelitian ini mengunakan metode deskritif dengan pendekatan kualitatif. Alat pengumpulan data yang digunakan adalah pedoman wawancara, observsi dan dokumentasi. Hasil penelitian menunjukkan bahwa  dalam mengatasi permasalahan membaca permulaan, guru berperan sebagai pembimbing, pelatih, dan pendamping  bagi kegiatan belajar siswa. Dalam perannya sebagai pembimbing, guru berusaha membimbing siswa agar dapat menemukan berbagai potensi yang dimilikinya, terutama potensi dalam membaca permulaan. Sebagai pelatih guru melatih peserta didik dalam pembentukan kompentensi dasar, sesuai dengan potensi masing-masing. Sebagai pendamping, guru mendampingi dan mengontrol siswa di dalam kelas agar hal yang disampaikan dalam proses kegiatan belajar mengajar dapat terlaksana dengan baik. Dalam proses belajar membaca, tahap awal adalah pengenalan huruf, kemudian pengabungan huruf vokal-konsonan menjadi suku kata dan kata serta gabungan kata menjadi kalimat sederhana. Selain itu, guru memberi contoh lafal  membaca suku kata, kata, dan  kalimat sederhana yang ditiru dan dihafalkan oleh siswa. Selanjutnya guru memberi tugas untuk dikerjakan di rumah dalam pendampingan orang tua, agar siswa semakin lancar dalam membaca dengan lafal yang benar.Kata Kunci: Peranan Guru,  Membaca Permulaan